Paesaggi fatti a mano. Didattica di architettura del paesaggio in situ - Occhipinti, Fausta (Ri-Vista. Research for landscape architecture, 2015)
The essay investigates the potential of teaching on site inside the school of landscape architecture, writing these reflections in the European debate on definition of teaching strategies, on the contents of the landscape architect’ s training and on the university pedagogy that now is under development. Many virtues of immersion and construction teaching on site for the learning of landscape project seems to be still explored and theorized. This approach, supplementary of teaching landscape project on office, put the student in his future field of action, concretely obliging him in transformation activities of spaces and introducing the “making” action, to stress the capability of real operations.